ANTIBACTERIAL EFFECTIVITY TEST OF ULIN BARK EXTRACT (Eusideroxylon zwageri) ON THE GROWTH OF Porphyromonas gingivalis - Della Isnadya Noor; I Wayan Arya Krishnawan Firdaus; Beta Widya Oktiani (FKG Unlam, 2021)
ABSTRACTBackground: Chronic periodontitis is an infectious disease caused by bacterial colonization of dental plaque. Bacteria that play a role in chronic periodontitis is Porphyromonas gingivalis. One of mouthwash that reduce the number of P.gingivalis colonies is chlorhexidine 0.2%. Long term use of chlorhexidine 0.2% can cause some side effects to the oral cavity, so we need an alternative mouthwash from natural ingredients that can reduce the side effects of chlorhexidine 0.2%. Ulin bark extract contains phenolic, flavonoid, tannin, alkaloid, terpenoid, and saponin which can be an alternative base for mouthwash besides chlorhexidine 0.2%. Purpose: It is to analyze antibacterial effectivity of ulin bark extract on the growth of Porphyromonas gingivalis. Methods: This study was using true experimental research and post-test only with control group design, that used 9 treatment groups with 4 replications, that were 5%, 10%, 20%, 40%, 60%, 80%, 100% concentrations, chlorhexidine 0.2%, and sterile aquadest against P. gingivalis. The total samples were as many as 36. Result: One Way ANOVA and Post-Hoc Games Howell tests showed that the average absorbance values has a significant difference, then Kruskall Wallis and Post Hoc Mann Whitney tests showed the number of colonies with significant differences. MIC in this study was at 5% concentration and MBC was at 20% concentration.. Conclusion: Ulin bark extract with 40% concentration has an absorbance value equivalent to 0.2% chlorhexidine and 20% concentration has a bactericidal effects equivalent to 0.2% chlorhexidine against the growth of P.gingivalis.Keywords:Antibacterial, Dilution method,Porphyromonas gingivalis, Ulin Bark Extract.